Distribution, Speciation and Bioaccumulation of Hg and As in Mariculture Sediments from Dongshan Bay, China. Issue 5 (3rd July 2016) - Du, Yongxiang; Meng, Fanping; Fu, Wenchao; Wang, Zhifeng
ABSTRACT: Hg and As are the major hazardous pollutants in marine sediments due to their high toxicity to benthonic organisms. Understanding the spatial distribution, speciation and bioaccumulation of these toxic elements in sediments is therefore of high environmental importance for identifying their potential risks. Sediments and bivalves Paphia undulata were collected from the mariculture area of Dongshan Bay, China, for characterizing geochemistry (by using the European Community Bureau of Reference (BCR) sequential extraction procedure) and bioaccumulation of Hg and As [by calculating the biota sediment accumulation factor (BSAF)]. Both elements in sediments were mostly associated with the residual fraction (69.52–95.06% and 88.22–91.12% of the total concentration, respectively), followed by the oxidizable (bound to sulfides and organic matter) fraction (1.25–25.32% and 3.62–6.00%, respectively). However, Hg presented a higher bioaccumulation than As. Correlation analysis indicated that As in residual fraction and Hg in oxidizable fraction exert positive contributions ( R = 0.927, P < 0.01 and R = 0.869, P < 0.05, respectively) on their own bioaccumulation factor. This indicated that P. undulata could adsorb both Hg in organic fraction and As in residual fraction from the sediments. Therefore, we should pay more attention to the potential dissolution and release of metals bound to sediments in the digestive tracts of marine organisms.